The Islamic traditions of Cirebon : ibadat and adat among Javanese muslims - Muhaimin, Abdul Ghoffir (Islam in Southeast Asia series (Canberra (A.C.T.)), 2006)
"This work deals with the socio-religious traditions of the Javanese Muslims living in Cirebon, a region on the north coast in the eastern part of West Java. It examines a wide range of popular traditional religious beliefs and practices. The diverse manifestations of these traditions are considered in an analysis of the belief system, mythology, cosmology and ritual practices in Cirebon. In addition, particular attention is directed to the formal and informal institutionalised transmission of all these traditions."--Publisher's description